Encapsulation of phase change materials by complex coacervation to improve thermal performances of woven fabrics - Önder, Emel; Çimen, Erhan; SARIER, NİHAL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
In this study, three types of paraffin waxes suitable for textile applications, namely n-hexadecane, n-octadecane and n-nonadecane were encapsulated through complex coacervation of natural and biodegradable polymers, gum arabic-gelatin mixture, in order to investigate their heat storing or releasing capacities, their durability as well as their practicable thermal performances when integrated into woven fabrics by coating. FT-IR results of capsules have presented the proofs of successful complex coacervation of PCMs. Most of the coacervates withstood considerable centrifugal forces in the leakage test and compression in coating applications of fabrics without resulting in any oil leak. DSC curves taken at 10 degrees C min(-1) and calorimeter measurements at the heating rate of 0.5-1 degrees C min(-1) of coacervates illustrate substantial endothermic enthalpies in the intervals corresponding to the phase transition interval of the paraffin wax used in a particular core, and tend to increase whereas the dispersed PCM contents in emulsions are relatively higher. One of the coacervates of n-hexadecane performed the enthalpy value of 144.7 J g(-1), while another coacervate containing n-octadecane provided 165.8 J g(-1) and the coacervate including n-nonadecane presented 57.5 J g(-1) enthalpy. When coacervates were, incorporated with woven fabrics, their feasible thermal performances appeared to be related to both actual paraffin wax content of the coacervate and the incorporation amount of it by the coating application. The energy absorption capacities of the coacervate added fabrics were found to be. 2.5-4.5 times enhanced relative to the reference fabric for particular temperature intervals. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: complex coacervation; gelatin; gum arabic; paraffin waxes; encapsulation; DSC; FT-IR; energy-storage; microencapsulation; microcapsules; proteins; gelatin; oil; karmaşık koaservasyon; jelatin; arap sakızı; parafın mumları; kapsülleme; enerji depolama; mikrokapsülleme; mikrokapsüller; proteinler; jelatin; yağ